The Chapel of La Misericordia in the Quarter of Flores, Buenos Aires - Manzi, Ofelia; Grau-Dieckmann, Patricia (Eikón / Imago, 2014)
One of the most interesting areas of research of the Gothic Revival in Argentina is the study of chapels built for the use of religious schools’ communities. Among these, the Chapel of La Misericordia helped to determine the scope and characteristics of the neo-Gothic style in Argentina. The windows are a recreation of the Gothic openings. Their decorative motifs derive from Winchester style manuscripts, while the figures clearly show Pre-Raphaelite reminiscences. This apparent aesthetic paradox conveys a message unchanged for centuries in a traditional medium such as a neo-Gothic cover, although adapted to the sentimental sensitivity for a girls’ school chapel. In this article we will focus on the iconographic analyses of the astounding stained-glass windows crafted in the 1930s by the Tiroler Glasmalerei Anstalt of Innsbruck.